Land Procurement for Public Interest and Spatial Planning: Legal and Juridical Implications - Edy Lisdiyono (APPTHI, 2017)
Population growth, industrial development, and national infrastructure made the government legislate Law No. 2 of 2012 concerning Land Acquisition for Development in the Public Interest. Apart from functioning as a catalyst for national development, this law also functions to manage spatial planning. This law is also related to land conversion and spatial planning, namely Law No. 26 of 2007 concerning Spatial Planning. Transfer of functions and spatial planning activities need to be synchronized in law to balance the need for land and to control the transfer of functions properly and in accordance with the spatial plan. Consequently, if there is a violation of the spatial plan that is not in accordance with its designation, both the permit giver and the user of the space, criminal sanctions must be applied to minimize the occurrence of land conversion. The Spatial Planning Law is ideal for realizing a safe, comfortable, productive, and sustainable national space based on the archipelago concept and national resilience. It is hoped that the dream of spatial planning can be achieved through the realization of harmony between the natural environment and the built environment, integration of the use of natural resources and artificial resources with due regard to human resources, and protection of spatial planning functions and prevention of negative impacts on the environment due to space utilization. Abstrak Pertambahan penduduk, perkembangan industri dan infrastruktur nasional membuat pemerintah mengundangkan Undang-Undang Nomor 2 Tahun 2012 tentang Pengadaan Tanah Untuk Pembangunan Untuk Kepentingan Umum. Selain berfungsi sebagai katalisator pembangunan nasional, undang-undang ini juga berfungsi untuk mengatur tata ruang. Undang-undang ini juga terkait dengan alih fungsi lahan dan tata ruang, yakni Undang-Undang Nomor 26 Tahun 2007 tentang Penataan Ruang. alih fungsi dan kegiatan penataan ruang perlu disinkronkan dalam undang-undang untuk menyeimbangkan kebutuhan tanah dan mengendalikan alih fungsi secara baik dan sesuai dengan rencana tata ruang. Konsekuensinya, jika terjadi pelanggaran terhadap rencana tata ruang yang tidak sesuai dengan peruntukannya, baik pemberi izin maupun pengguna ruang harus dikenakan sanksi pidana dengan tujuan untuk meminimalisir terjadinya alih fungsi lahan. UU Penataan Ruang sangat ideal untuk mewujudkan ruang nasional yang aman, nyaman, produktif, dan berkelanjutan berlandaskan konsep nusantara dan ketahanan nasional. Harapan penataan ruang yang dicita-citakan dapat tercapai melalui terwujudnya keselarasan antara lingkungan alam dan lingkungan binaan, keterpaduan pemanfaatan sumber daya alam dan sumber daya buatan dengan memperhatikan sumber daya manusia, dan perlindungan fungsi tata ruang dan pencegahan dampak negatif terhadap lingkungan akibat pemanfaatan ruang. Kata Kunci: Kepentingan Umum, Pengadaan Tanah, Penataan Ruang, UU No. 26 Tahun 2007